Differentinating between non-transfusion dependant β-thalassemia and iron deficinecy anemia in children using ROC and logistic regression analysis: two novel discrimination indices designed for pediatric patients - Turudic, Daniel; Vucak, Jerko; Kocheva, Svetlana; Milosevic, Danko; Bilic, Ernest (Frontiers in Pediatrics, 2024)
This cross-sectional study enrolled a group of 271 children with microcytic anemia in order to test the performance of 41 single and 2 composite formulas andindices in distinguishing between β-thalassemia (β-thal) and iron deficiency anemia (IDA) in the pediatric population. Optimal pediatric cut-off values from the previously published formulas and indices were generated using ROC analysis.Formulasand indices with optimal cut-offvalues in children with accuracy ≥ 90% were (in descending order): Matos & Carvalho index,MDHL(Telmissani) formula, England and Fraser formula, Pornprasert index, Sirachainan index, Telmissani (MCHD) formula, CRUISE index,Hameed index,Sargolzaie formulaand Zaghloul II index. Logistic regression in R using generalized linear models (glm) generated two new indices. The CroThalDD-LM1 index has an accuracy of 93.36% (AUC 0.986, 95% CI 0.975-0.997), while the second CroThalDD-LM2 index utilizes absolute reticulocyte count alongside CBC variables, with an accuracy of 96.77% (AUC 0.985, 95% CI 0.988 - 0.999). These are the first discrimination indices generated and designed precisely for the pediatric population, which includes preschool children. We recommend using aforementioned formulas and indices with corrected cut-off values and accuracy > 90% alongside two new proposed indices. A comparison of both native and these new indices is encouraged.